Pengaruh Penggunaan Gawai Dan Interaksi Ibu-Anak Terhadap Perkembangan Sosial-Emosional Anak Prasekolah Di PMB Eka Herlina Desa Cikareo - Hernanda, Assyiffa; Futriani, Elfira Sri (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The process of early introduction of gadgets to children and toddlers has a big impact on their attitude patterns in daily activities. The ability to think and behave as well as the ability to build a positive concept of identity from an early age will all be negatively affected. . Curiosity tends to be high when they are children, but this will be affected by the bad effects of using gadgets. This research aims to analyze the influence of device use and mother-child interactions on the social-emotional development of preschool children Methods: This research is a quantitative study, using a descriptive analytical design using a cross sectional method. The population in this study were all preschool children/toddlers (3-6 years) in PMB Eka Herlina, Cikareo Village, Lebak Regency, Banten, in 2023, totaling 35 people. The sample used in this research was total sampling. The instrument that will be used in this research is a questionnaire. The statistical test used is the Wilcoxon Test. Results: There was a level of increase in social-emotional development before and after using the device, the results of the Wilcoxon test analysis were obtained, a significance value of 0.03 (p<0.05) and there was a decrease in the interaction between mother and child before and after using the device, the results of the Wilcoxon test were obtained significance value 0.00 (p<0.05) Conclusion: Social - Emotional influences the use of devices and there is an influence of mother and child interactions on the use of devices